Recycling of bamboo leaves and use as pozzolanic material to mitigate degradation of cementitious composites - Nehring, Victor; Silva, Lucas Henrique Pereira; de Maria, Vitor Peixoto Klienchen; de Paiva, Fabio Friol Guedes; Tamashiro, Jacqueline Roberta; dos Santos, Luis Fernando [UNESP]; Teixeira, Silvio Rainho [UNESP]; Kinoshita, Angela (Elsevier, 2022)
The search for agro-industrial residues as supplementary cementitious materials has intensified as a result of the desire for more sustainable products and a reduction in the environmental effect of non-renewable natural resource exploitation. Pozzolanic materials offer a series of advantages, among them, the reduction of porosity and improvement to the attack of external agents, such as the acids present in the rains of industrial regions that accelerate the degradation of concrete structures. Several agro-industrial residues have been studied, including bamboo leaf ash (BLA), which has shown positive results in terms of reactivity and compressive strength. The objective of this work was to evaluate the ability of BLA to act as a mitigating agent of acid attack when incorporated to mortars. The BLA was produced by self-combustion and the physical chemical analysis showed the formation of amorphous material, with a predominance of silicon oxide. BLA was used to partially replace Portland cement ARI V, at 20 % and 30 %, in the manufacture of mortars. Prismatic specimens of the reference and experimental mortars were cured in an acid environment (5 % sulfuric acid). The mechanical tests of resistance to bending and compression, at 7 and 28 days of curing, show that there was no change in these properties, as a result of the replacement (p > 0.05). However, when evaluating the loss of mass of the specimens, it was observed that the reference specimens suffered greater loss in relation to those constituted by BLA, in both percentages (p < 0.05). In this way, the results of this work demonstrate the feasibility of using BLA as a substitute for Portland cement, with environmental gains, due to use of waste, economy of non-renewable raw materials and energy, in addition to the advantage of mitigating the effects of acid attack on mortars.
Keywords: Bamboo leaf ash; Chemical attack; Durability; Mortar; Pozzolanic additions